ANALYSIS OF THE CAUSES OF DECREASED LUBRICATING OIL PRESSURE IN THE TONASA LINES XII AIRCRAFT CARRIER ENGINE - Eko Nugroho Widjatmoko; P Marcello Lopulalan; Driaskoro Budi Sidharta; Eko Prasetio (Sean Institute, 2023)
The lubrication system on the main engine plays a crucial role in maintaining optimal engine performance during operation. Its function is to lubricate moving engine components, lower engine temperature, reduce vibration, and protect core components from corrosive substances so that engine performance will always be maintained and can support the smooth operation of the ship, from the researcher's observation of the mother machine in KM. Tonasa Lines found that the main engine had a problem with the lubricating oil part, namely the dropped lubricating oil pressure. This study is directed to determine the cause, impact of the pressure drop, and handling steps so that the main machine can work normally again. This study applied the FTA (Fault Tree Analysis) method to understand the causes and effects of decreased lubricating oil pressure. The results showed that the decrease in lubricating oil pressure was caused by a pump not functioning optimally and blockages in the lubricating oil filter. This results in inefficient lubrication of the main engine. Decreased lubricating oil pressure that reaches 2.0 kg/cm2 increases the main engine's temperature. The recommended solution to restore the lubricating oil pressure to the normal pressure of 3.0 kg/cm2 is to add lubricating oil to the degraded/reduced Lubricating Oil Tank. In addition, it is important always to ensure the cleanliness of lubricating oil filters, monitor pump RPM through routine maintenance, and document any incidents in log books.